Investigation of immobilization and hydrolytic properties of pectinase onto chitosan-PVA copolymer - Kaur, Inderjeet; Gupta, Reena; Lakhanpal, Anupam; Kumar, Atul (International Journal of Advanced Chemistry, 2014)
Copolymer based on natural polysaccharide, Chitosan, Chs and synthetic polymer, poly vinyl alcohol, PVA was synthesized using ammonium persulfate as radical initiator and sodium bicarbonate as foaming agent. Reaction conditions were optimized based on swelling percentage of copolymer. The copolymer, (Chs-co-PVA), was characterized by FTIR, SEM and XRD methods and was used as a support for immobilizing pectinase. The immobilized enzyme was found to be more stable than free enzyme and has a good binding efficiency (88.29%) with the copolymer. The effect of temperature, pH and metal ions on the activity of the bound enzyme towards hydrolysis of poly-?-(1-4)-D-galacturonic acid (PGA) was investigated. Keywords: Chitosan-PVA Copolymer, Pectinase, Immobilization, Hydrolysis, Polygalacturonic Acid.